MYC dosage compensation is mediated by miRNA-transcription factor interactions in aneuploid cancer - Acón Chan, Man Sai (2021)
We hypothesize that dosage compensation of critical genes arises from systems- level properties for cancer cells to withstand the negative effects of aneuploidy. We identified several candidate genes in cancer multiomics data and developed a biocomputational platform to construct a mathematical model of their interac- tion network with micro-RNAs and transcription factors, where the property of dosage compensation emerged for MYC and was dependent on the kinetic pa- rameters of its feedback interactions with three micro-RNAs. These circuits were experimentally validated using a genetic tug-of-war technique to overex- press an exogenous MYC, leading to overexpression of the three microRNAs involved and downregulation of endogenous MYC. In addition, MYC overexpres- sion or inhibition of its compensating miRNAs led to dosage-dependent cytotoxicity in MYC-amplified colon cancer cells. Finally, we identified negative correlation of MYC dosage compensation with patient survival in TCGA breast cancer patients, highlighting the potential of this mechanism to prevent aneu- ploid cancer progression.